Impact of ownership type and firm size on organizational culture and on the organizational culture-effectiveness linkage - Zeng, Kaisheng; Luo, Xiaohui (Journal of Business Economics and Management, 2013)
This paper aims to extend the extant (primarily Western) organizational culture literature to emerging economies by explicitly incorporating two key contextual variables-ownership type and firm size into organizational culture model. Based on the theoretical model developed by Denison and his colleagues, we examined the impact of ownership type and firm size on organizational culture, as well as the moderating effect of the two contextual variables on the linkage between organizational culture and firm effectiveness. Using survey data from foreign-invested and state-owned firms in China, we find that ownership type and firm size have significant influence on organizational culture. We also find that different ownership type and firm size result in different organizational cultural effect on performance.